STRUGGLE FOR UKRAINIAN LANGUAGE AS A WAY OF SAVING NATIONAL IDENTITY IN 1919–1939 (ON THE EXAMPLE OF STANISLAVIV DISTRICT) - Puyda, R. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Features of Ukrainian national-cultural life as a part of the Second Polish Republic (1919–1939) on the example of Stanislaviv district are considered in this article. The basic aspects of the state policy of the Polish authorities concerning national minorities, particularly, in education, are described. The main goal of this policy was assimilation of the local population through displacement of Ukrainian language from the most important sectors of public life.